The role of faith-based organisations in peacebuilding in Mt Elgon region - MUNG’OU, CHEROTICH; KWANYA, DR TOM; OSODO, DR JOSEPH (kabarak university, 2016)
Peace is defined as the absence of term is derived from Galtung’s (1976 violence, social justice and ecological of war by addressing the root causes The former UN Secretary General Agenda for Peace defined peace building support structures which would tend order to avoid a relapse into conflict According to Jeong (2003)
Keywords: The role of faith-based organisations; peacebuilding in Mt Elgon region